First remingtonocetid archaeocete (Mammalia, Cetacea) from the middle Eocene of Egypt with implications for biogeography and locomotion in early cetacean evolution. (21st March 2016) - Bebej, Ryan M.; Zalmout, Iyad S.; Abed El-Aziz, Ahmed A.; Antar, Mohammed Sameh M.; Gingerich, Philip D.
Abstract: Remingtonocetidae are Eocene archaeocetes that represent a unique experiment in cetacean evolution. They possess long narrow skulls, long necks, fused sacra, and robust hind limbs. Previously described remingtonocetids are known from middle Eocene Lutetian strata in Pakistan and India. Here we describe a new remingtonocetid, Rayanistes afer, n. gen. n. sp., recovered from a middle to late Lutetian interval of the Midawara Formation in Egypt. The holotype preserves a sacrum with four vertebral centra; several lumbar and caudal vertebrae; an innominate with a complete ilium, ischium, and acetabulum; and a nearly complete femur. The ilium and ischium of Rayanistes are bladelike, rising sharply from the body of the innominate anterior and posterior to the acetabulum, and the acetabular notch is narrow. These features are diagnostic of Remingtonocetidae, but their development also shows that Rayanistes had a specialized mode of locomotion. The expanded ischium is larger than that of any other archaeocete, supporting musculature for powerful retraction of the hind limbs during swimming. Posteriorly angled neural spines on lumbar vertebrae and other features indicate increased passive flexibility of the lumbus. Rayanistes probably used its enhanced lumbar flexibility to increase the length of the power stroke during pelvic paddling. Recovery of a remingtonocetid in Egypt broadens the distribution of Remingtonocetidae and shows that protocetids were not the only semiaquatic archaeocetes capable of dispersal across the southern Tethys Sea.